Differences in Financial Actions between Chapter 13 Bankruptcy Filers and Non-filers - Williams, Albert A.; Kehiaian, Scott E.; Bird, Carolyn L. (Journal of Applied Business and Economics, 2017)
We determine that there are significant differences in 21 of 28 financial actions between Chapter 13 bankruptcy filers and non-filers living in the Middle District of North Carolina. The significant financial actions fall in the following areas: goal planning, income, budgeting, purchasing, insurance, credit, savings, retirement, and mortgages. The results of this study can be used to get a deeper insight into bankruptcy characteristics. They can also be used to restructure financial literacy education efforts to reduce personal bankruptcy.